2012
DOI: 10.1371/journal.pone.0052815
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Laser Endomicroscopy for the Morphometric Evaluation of Microvessels in Human Colorectal Cancer Using Targeted Anti-CD31 Antibodies

Abstract: IntroductionNumerous anti-angiogenic agents are currently developed to limit tumor growth and metastasis. While these drugs offer hope for cancer patients, their transient effect on tumor vasculature is difficult to assess in clinical settings. Confocal laser endomicroscopy (CLE) is a novel endoscopic imaging technology that enables histological examination of the gastrointestinal mucosa. The aim of the present study was to evaluate the feasibility of using CLE to image the vascular network in fresh biopsies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…CD31 is a pan-endothelial marker for small and large vessels (29). In order to assess the MVD, CD31 and associated antibodies are used to mark tumor vascular endothelial cells and the capillary number per unit area is counted (30). In the present study, immunohistochemical staining for CD31 revealed that the average MVD in the pLXSN-Tum-5 group was significantly lower compared with that in the pLXSN and wild-type H22 HCC groups.…”
Section: Discussionsupporting
confidence: 47%
“…CD31 is a pan-endothelial marker for small and large vessels (29). In order to assess the MVD, CD31 and associated antibodies are used to mark tumor vascular endothelial cells and the capillary number per unit area is counted (30). In the present study, immunohistochemical staining for CD31 revealed that the average MVD in the pLXSN-Tum-5 group was significantly lower compared with that in the pLXSN and wild-type H22 HCC groups.…”
Section: Discussionsupporting
confidence: 47%
“…Afterwards, the excess antibodies were washed away in saline and the samples were immediately visualized in CLE imaging to assess the microvascularization ex vivo up to a maximum depth of 250 μm. CLE images were acquired using Pentax EC-3870 CIFK, Tokyo, Japan, a dedicated endomicroscopy system with an excitation wavelength of 488 nm and with a maximum laser power output of ≤ 1 mW at the surface of the tissue [16,17] . To assess both endothelial markers more accurately, we used the color overlay function in the ImageJ image processing software (National Institutes of Health, United States).…”
Section: Targeted Anti-cd105 Antibodies For Cle Imaging Of Normal Colmentioning
confidence: 99%
“…To confirm the role of CD105 vs CD31 in tumor neoangiogenesis, adjacent samples from the same patient were processed for immunohistochemistry, for normal and tumor samples as described previously [16,17] . Briefly, after formaldehyde fixation and paraffin embedding, 4 μm tissue sections were sliced from these blocks, deparaffinized, re-hydrated and processed for antigen retrieval by microwaving for 20 min in citrate buffer pH 6.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we showed that the CLE method is feasible for imaging different aspects of the tumor vasculature from fresh biopsy samples similar to the currently accepted histopathology techniques [9]. In this study, we evaluated new vascular network parameters difficult to assess with conventional immunohistochemistry in patients with clinically staged T3 primary colorectal carcinoma, without metastatic spread, by using CLE combined with fluorescently labeled anti-CD31 antibodies for labeling of both normal and tumor blood vessels.…”
Section: Introductionmentioning
confidence: 98%